Impact of Adjuvant Chemoradiotherapy on Survival of Resected Pancreatic Adenocarcinoma Cancer: A Surveillance, Epidemiology and End Results (SEER) Analysis - Shi, Xiaomao; Peng, Jin; Jiang, Huangang; Gao, Yu; Wang, Wenbo; Zhou, Fuxiang (Frontiers in Oncology, 2021)
Background The benefits of postoperative adjuvant chemoradiotherapy (CRT) for pancreatic cancer remain controversial. The purpose of this study is to determine if adjuvant CRT can improve the overall survival of postoperative pancreatic cancer patients compared to adjuvant chemotherapy (CT). Methods Patients with resected pancreas adenocarcinoma were identified in the Surveillance, Epidemiology, and End Results (SEER) database (2004–2016). Multivariate Cox regression was used to determine the factors related to survival rate. Selection bias was reduced to a minimum through propensity matching analysis. Subgroup analyses by clinical characteristics were performed. Results This study identified 10,097 patients who received adjuvant CT (n = 5,454) or adjuvant CRT (n = 4,643). On multivariate analysis, age, sex, tumor size, site, grade, stage, T stage, and lymph node metastasis were independent risk factors for OS. The basic clinical characteristics were well balanced after propensity matching. After propensity matching, CRT can improve the survival rate compared with CT [median OS: 22 months vs 23 months (HR, 0.928; 95% CI, 0.881–0.977; P = 0.004)]. Subgroup analysis indicated that the survival benefit of adjuvant chemoradiotherapy was more significant in patients with female (HR, 0.860; 95% CI, 0.798–0.926; P = 0.005 for interaction) or T3 (HR, 0.905; 95% CI, 0.855–0.957; P = 0.04 for interaction) or lymph nodes positive (HR, 0.883; 95% CI, 0.832–0.938; P = 0.005 for interaction). Conclusion Adjuvant CRT was associated with improved survival compared with adjuvant CT in patients with resection of pancreatic ductal adenocarcinoma. The benefit was more significant in patients with female or T3 or lymph nodes positive.